Shear Stress Induces Differentiation of Endothelial Lineage Cells to Protect Neonatal Brain from Hypoxic-Ischemic Injury through NRP1 and VEGFR2 Signaling. (5th October 2015) - Huang, Chia-Wei; Huang, Chao-Ching; Chen, Yuh-Ling; Fan, Shih-Chen; Hsueh, Yuan-Yu; Ho, Chien-Jung; Wu, Chia-Ching
Abstract : Neonatal hypoxic-ischemic (HI) brain injuries disrupt the integrity of neurovascular structure and lead to lifelong neurological deficit. The devastating damage can be ameliorated by preserving the endothelial network, but the source for therapeutic cells is limited. We aim to evaluate the beneficial effect of mechanical shear stress in the differentiation of endothelial lineage cells (ELCs) from adipose-derived stem cells (ASCs) and the possible intracellular signals to protect HI injury using cell-based therapy in the neonatal rats. The ASCs expressed early endothelial markers after biochemical stimulation of endothelial growth medium. The ELCs with full endothelial characteristics were accomplished after a subsequential shear stress application for 24 hours. When comparing the therapeutic potential of ASCs and ELCs, the ELCs treatment significantly reduced the infarction area and preserved neurovascular architecture in HI injured brain. The transplanted ELCs can migrate and engraft into the brain tissue, especially in vessels, where they promoted the angiogenesis. The activation of Akt by neuropilin 1 (NRP1) and vascular endothelial growth factor receptor 2 (VEGFR2) was important for ELC migration and following in vivo therapeutic outcomes. Therefore, the current study demonstrated importance of mechanical factor in stem cell differentiation and showed promising protection of brain from HI injury using ELCs treatment.